2022
DOI: 10.3390/cells11030548
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Activates Germline and Cleavage Embryo Genes in Mouse Embryonic Stem Cells

Abstract: Lactate was recently found to mediate histone lysine lactylation and facilitate polarization of M1 macrophages, indicating its role in metabolic regulation of gene expression. During somatic cell reprogramming, lactate promotes histone lactylation of pluripotency genes and improves reprogramming efficiency. However, the function of lactate in cell fate control in embryonic stem cells (ESCs) remains elusive. In this study, we revealed that lactate supplementation activated germline genes in mouse ESCs. Lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…Followed by the metabolic remodeling, Glis1 quickly activates glycolysis, thus enhancing histone lactylation (H3K18la), opening pluripotency genes, promoting senescent cell reprogramming and improving the genome stability of the induced pluripotent stem cells. Similarly, another study observed the upregulation of germline and cleavage embryo genes in mouse embryonic stem cells after the accumulation of histone Kla (Tian and Zhou, 2022). Further analysis revealed that the remarkably increased deposition of H3K18la at the transcription start site might be responsible for the sequential activation of germline and zygotic genome activation genes.…”
Section: Lactylation and Cell Fate Determinationmentioning
confidence: 80%
See 1 more Smart Citation
“…Followed by the metabolic remodeling, Glis1 quickly activates glycolysis, thus enhancing histone lactylation (H3K18la), opening pluripotency genes, promoting senescent cell reprogramming and improving the genome stability of the induced pluripotent stem cells. Similarly, another study observed the upregulation of germline and cleavage embryo genes in mouse embryonic stem cells after the accumulation of histone Kla (Tian and Zhou, 2022). Further analysis revealed that the remarkably increased deposition of H3K18la at the transcription start site might be responsible for the sequential activation of germline and zygotic genome activation genes.…”
Section: Lactylation and Cell Fate Determinationmentioning
confidence: 80%
“…Of note, during somatic reprogramming, H3K18la tended to be highly enriched at the promoters of pluripotency genes, such as Octamer-binding transcription factor 4 (Oct4), spalt like transcription factor 4 (Sall4) and MYCN proto-oncogene (Mycn), which subsequently upregulated their expressions (Li et al, 2020). In contrast, the expression of pluripotent genes, including Oct4, Nanog homeobox (Nanog), and SRY-box transcription factor 2 (Sox2), were not affected upon lactate supplementation in mouse embryonic stem cells (Tian and Zhou, 2022). That is, lactate strengthened H3K18la without affecting pluripotency of mouse embryonic stem cells.…”
Section: Lactylation and Cell Fate Determinationmentioning
confidence: 98%
“…Additionally, hypoxia reduces the activity of LDHA, which reduces lactate production. Moreover, another study showed that the accumulation of H3K18la on germline and cleavage embryo genes promotes transcriptional elongation ( Tian and Zhou, 2022 ). The authors found that adding lactate activated the germline genes and cleavage embryo genes in mouse embryonic stem cells (ESCs).…”
Section: Lactylation and Diseasesmentioning
confidence: 99%
“…It was recently revealed that lactate and lactate-induced histone lactylation are also involved in cell fate conversion in mouse ESCs [ 86 ]. Exogenous lactate stimulates the lactylation of histone lysine residues [ 87 ], and lactate treatment for 24 h significantly improved lactylation of H3K18 (H3K18la) in ESCs [ 86 ].…”
Section: The Strategies Used For Inducing 2clcs May Improve Scnt Effi...mentioning
confidence: 99%
“…It was recently revealed that lactate and lactate-induced histone lactylation are also involved in cell fate conversion in mouse ESCs [ 86 ]. Exogenous lactate stimulates the lactylation of histone lysine residues [ 87 ], and lactate treatment for 24 h significantly improved lactylation of H3K18 (H3K18la) in ESCs [ 86 ]. Findings from chromatin immunoprecipitation-sequencing and RNA-sequencing analysis of mouse ESCs found a positive correlation between H3K18la intensity and transcript abundance.…”
Section: The Strategies Used For Inducing 2clcs May Improve Scnt Effi...mentioning
confidence: 99%